顔面軟部組織に発生したランゲルハンス細胞組織球症の1例 - 伊原木, 聰一郎; 吉岡, 徳枝; 小野, 喜章; 長塚, 仁; 増井, 正典; 佐々木, 朗 (日本口腔外科学会雑誌, 2023)
Langerhans cell histiocytosis (LCH) is a rare proliferative disorder characterized by the accumulation of Langerhans cells, and wide-ranging organ involvement. In the oral and maxillofacial region many cases have been reported in the hard tissue of jaws; cases occurring in facial soft tissue are rare. We report a case of LCH arising in the facial soft tissue of a 26-year-old man who presented with an ulcerative lesion on the lower lip and erythema around the left eyelid skin.　Tissue biopsies of both the lower lip and left eyelid skin lesions were performed, and a histological diagnosis of LCH was obtained for both lesions. The lesion on the lower lip was treated by corticosteroid injection, and the lesion around the left eyelid skin was treated by corticosteroid ointment. One month later, the lesion on the lower lip had shrunk, and the lesion around the left eyelid was improving. The patient was followed up for eight years after the treatment, and there was no recurrence or appearance of lesions in any other organs. Although skin-mucosal limited LCH usually indicates an indolent clinical course, there is a secondary risk of developing hematopoietic tumors and long-term follow-up is required.